Anticorrosive iron powder as well as preparation method and application thereof
By adopting a double-layer protective structure on the iron powder, a combination of tung oil layer and an anti-rust oil layer, the problem of oxidation and corrosion of iron powder in humid environments is solved, the anti-corrosion performance of iron powder and the setting effect of fireworks is improved, and the fireworks are set to ensure that Safety and stability.
Patent Information
- Application Number
- CN202411284846.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-03
AI Technical Summary
Iron powder is easily oxidized in humid environments due to reaction with perchlorate oxidants in fireworks, resulting in corrosiveness reducing combustion efficiency and increasing safety hazards. The existing anticorrosion measures fail under high temperature conditions or increase production costs.
Adopt a double-layer protection structure, the tung oil layer and the anti-rust oil layer are successively coated with the iron powder particle matrix. The thickness of the tung oil layer is greater than the anti-rust oil layer, providing protection against water and oxygen, and supplementing protection against the anti-rust oil layer to enhance the chlorine resistance of the iron powder. Ion corrosion capability.
It significantly improves the anti-corrosion performance of iron powder, ensures stability and safety under a variety of environmental conditions, extends service life, reduces performance degradation and safety hazards caused by corrosion, and improves the setting effect and ornamental value of fireworks.
Smart Images

Figure CN119237731A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fireworks preparation, and in particular relates to anti-corrosion iron powder and a preparation method and application thereof. Background Art
[0002] As a celebratory and entertaining product with traditional cultural significance, the beautiful colors and brilliant effects of fireworks are inseparable from the exquisite proportion of chemical raw materials. The main components of fireworks include oxidants, combustion aids and color developers. Among them, iron powder, as a commonly used basic material, has an important influence on the effect of fireworks. Iron powder can not only enhance the brightness of fireworks, but also improve the color effect of fireworks. However, in the actual application of fireworks, the stability and safety of iron powder face many challenges, which requires effective anti-corrosion treatment of iron powder to ensure the safety and performance of fireworks.
[0003] The main role of iron powder in fireworks is to participate in the combustion reaction as a combustible and emit a dazzling yellow light during the combustion process. The introduction of iron powder can enhance the visual effect of fireworks and make them more eye-catching in the night sky. Specifically, iron powder reacts with oxidants when fireworks are set off, releasing a large amount of heat and making the light of fireworks brighter. The application of iron powder can make fireworks present richer color levels and stronger visual impact, thereby improving the ornamental value of fireworks. Although iron powder has a significant effect in fireworks, its application also faces some technical difficulties. The main problem is the corrosiveness of iron powder, especially the stability of iron powder in a humid environment. Iron powder needs to be mixed with oxidants such as perchlorates during the manufacturing process of fireworks, and these oxidants often contain perchlorate ions. Under humid environmental conditions, perchlorate ions easily undergo redox reactions with iron powder to generate ferric chloride. Ferric chloride is not only highly corrosive, but also causes oxidation of iron powder, thereby reducing its combustion efficiency and affecting the performance of fireworks. In addition, the heat and volume expansion generated by ferric chloride during the reaction process may cause damage or failure of fireworks materials, increasing safety risks. These problems are particularly evident in maritime transportation and humid climate conditions. The corrosion of iron powder will not only reduce the effect of fireworks, but may also cause the overall performance of fireworks to decline, and even cause safety accidents.
[0004] In order to deal with the problem of iron powder corrosion, researchers and manufacturers have taken some measures to improve the stability of iron powder. One common practice is to modify the surface of iron powder to reduce its sensitivity to chloride ions. For example, by coating a protective film on the surface of iron powder, the contact between iron powder and the external environment can be effectively isolated, reducing the occurrence of corrosion reactions. Another method is to improve the production process of iron powder so that it can form a more stable structure during the manufacturing process, thereby improving its corrosion resistance. Although these methods have alleviated the corrosion problem of iron powder to a certain extent, there are still some technical bottlenecks. For example, the existing protective film materials may fail under high temperature conditions, affecting the burning effect of fireworks. At the same time, surface modification treatment may increase production costs and affect the quality of iron powder. In addition, how to further improve the anti-corrosion performance of iron powder while ensuring the effect of fireworks is still a technical problem that needs to be solved urgently. Summary of the invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides an anti-corrosion iron powder, which further improves the anti-corrosion performance of the iron powder while ensuring the fireworks effect.
[0006] The invention also provides a method for preparing the anticorrosive iron powder.
[0007] The invention also provides a firework.
[0008] The first aspect of the present invention provides an anti-corrosion iron powder, comprising an iron powder particle matrix, the surface of the iron powder particle matrix is sequentially coated with a raw tung oil layer and an anti-rust oil layer, and the thickness of the raw tung oil layer is greater than the thickness of the anti-rust oil layer.
[0009] One of the technical solutions of the present invention regarding the anti-corrosion iron powder has at least the following beneficial effects:
[0010] The core of the anti-corrosion iron powder of the present invention lies in the double-layer protection structure on its surface, including a raw tung oil layer and an anti-rust oil layer. This double-layer protection mechanism provides two layers of protection, specifically:
[0011] Raw tung oil (also known as tung oil) is a natural vegetable oil with excellent anti-corrosion properties. The raw tung oil layer is relatively thick, which enables it to effectively isolate air and moisture, thereby preventing the iron powder from coming into contact with oxygen and moisture during storage and use. The drying and anti-corrosion properties of tung oil can effectively delay the oxidation of iron powder and reduce the occurrence of corrosion. Raw tung oil has the characteristics of fast drying, good fluidity and strong adhesion. It can penetrate the irregular surface of iron powder very well and achieve full wrapping; after coating, anti-rust oil is added. Using the principle of similar compatibility, the interface between the anti-rust oil and tung oil will form a mutually soluble structure, and there is no obvious interface, which enhances the adhesion of the coating. The prepared coating layer has a large thickness, good density, good water and oxygen barrier capabilities and stability, thereby improving the iron powder material's ability to resist salt water and salt spray corrosion for a long time.
[0012] Anti-rust oil is a kind of grease specially used to prevent metal corrosion, which is usually thin. The anti-rust oil layer can further provide protection to prevent iron powder from rusting during long-term storage and transportation. Since the anti-rust oil layer is thinner than the raw tung oil layer, it mainly plays a supplementary protective role and will not affect the main protective function of the raw tung oil layer.
[0013] The thickness of the raw tung oil layer is greater than the anti-rust oil layer. This design ensures a long-lasting and comprehensive anti-corrosion effect. The thickness of the raw tung oil layer can effectively prevent the intrusion of moisture and oxygen, while the anti-rust oil layer provides additional protection and enhances the comprehensive anti-corrosion performance of the iron powder. This structure can not only prevent short-term corrosion, but also improve the stability of the iron powder during long-term storage and transportation.
[0014] The anti-corrosion iron powder of the present invention can exhibit excellent anti-corrosion performance under various environmental conditions. For example, in a humid environment, the tung oil layer can effectively prevent the intrusion of moisture, while the anti-rust oil layer can deal with other potential corrosion sources. This adaptability enables the iron powder to maintain good performance under different storage and use conditions.
[0015] Due to the double layer protection, the anti-corrosion iron powder of the present invention is more stable during transportation and storage. During transportation, especially in a humid or high temperature environment, the double protection of the thickness of the raw tung oil layer and the anti-rust oil layer can reduce the corrosion risk of the iron powder and reduce the safety hazards caused by the degradation of the performance of the iron powder.
[0016] In the application of fireworks, the stability of iron powder directly affects the effect of fireworks. If the iron powder is oxidized or corroded during use, the light effect of the fireworks will decrease, or even abnormal firing will occur. Through the double-layer anti-corrosion treatment of the present invention, the iron powder can maintain good performance during long-term storage and transportation, thereby ensuring that the effect of fireworks is not affected. Furthermore, through effective anti-corrosion treatment, the service life of the iron powder is extended. This not only improves the comprehensive performance of the iron powder, but also reduces the additional cost caused by material corrosion, making the production and use of fireworks more economical and reliable.
[0017] Thus, the anti-corrosion iron powder of the present invention provides excellent anti-corrosion performance through the dual protection of the raw tung oil layer and the anti-rust oil layer. The thick protection of the raw tung oil layer ensures the long-term stability of the iron powder, while the anti-rust oil layer further enhances the protective effect. This design not only improves the storage and transportation stability of the iron powder, but also ensures the firing effect of the fireworks in actual use, thereby improving the quality and safety of the fireworks.
[0018] According to some embodiments of the present invention, the particle size of the iron powder particle matrix is 100 micrometers to 300 micrometers.
[0019] The particle size of the iron powder matrix is in the range of 100 to 300 microns, which optimizes the combustion effect. The iron powder particle size of 100 to 300 microns is moderate, which is neither as easy to form excessive dust as too fine powder, nor as difficult to burn evenly as too large particles. The moderate particle size can ensure that the iron powder burns more evenly and stably during the fireworks, enhancing the light effect and effect of the fireworks. Medium-sized iron powder particles can effectively dissipate heat and produce more dazzling light during the combustion process. Too fine particles may cause too fast combustion and reduce the brightness; too large particles may cause incomplete combustion and insufficient brightness. The moderate particle size can provide the best light effect.
[0020] The particle size of the iron powder particle matrix ranges from 100 microns to 300 microns, which improves the stability of the fireworks. Iron powder with medium particle size is not easy to form a large amount of dust in the air, and has a lower risk of flying and volatilization than finer powders. This reduces the risk of dust generated during manufacturing, storage and transportation, thereby improving the safety of operations. Particles that are too small are prone to static electricity, increasing safety hazards; particles that are too large are difficult to mix evenly, affecting the performance of fireworks. Medium particle size iron powder provides a good balance to ensure the stability of the material.
[0021] The particle size of the iron powder particle matrix ranges from 100 microns to 300 microns, which improves the material's handling and processing properties. Medium-sized iron powder can be mixed well with other fireworks ingredients (such as oxidizers and developers). Particles that are too large may cause uneven mixing and affect the final firing effect; while particles that are too small may increase processing difficulty and cost. Iron powder of this size is easier to handle during production and processing, which can improve production efficiency and reduce production costs. The moderate particle size ensures consistency and stability during mixing, pressing and other processing processes.
[0022] The particle size of the iron powder particle matrix is in the range of 100 microns to 300 microns, which optimizes the anti-corrosion performance. The particle size of 100 microns to 300 microns can effectively adapt to the coating of the anti-corrosion coating. For example, the protective layer formed by the raw tung oil layer and the anti-rust oil layer on the surface of the iron powder of this particle size is uniform and effective, providing a good anti-corrosion effect. If the particle size is too small, the coating may not be evenly distributed, and if the particle size is too large, the coating may not adhere firmly. Through the appropriate particle size, the protective effect of the anti-corrosion layer can be optimized, thereby extending the service life of the iron powder and reducing performance degradation and safety hazards caused by corrosion.
[0023] The particle size of the iron powder matrix is in the range of 100 microns to 300 microns, which improves the visual effect of fireworks. The appropriate particle size can produce uniform light and color effects in fireworks. Too small particle size may cause uneven light scattering, while too large particle size may cause unstable combustion effect. The appropriate iron powder particles can provide a more stable and bright visual effect, improving the viewing value of fireworks.
[0024] Therefore, the particle size of the iron powder particle matrix in the range of 100 microns to 300 microns provides multiple beneficial effects, including optimizing combustion effects, improving the stability of fireworks, enhancing the handling of materials, optimizing anti-corrosion performance, and enhancing the visual effects of fireworks. This particle size of iron powder can achieve the best combustion effect and performance while ensuring safety and processing efficiency, and is the appropriate particle size range.
[0025] According to some embodiments of the present invention, the particle size of the iron powder particle matrix is any value of 100 microns, 150 microns, 200 microns, 250 microns, 300 microns, or a range formed by any two of them, such as 150 microns to 250 microns.
[0026] According to some embodiments of the present invention, the raw tung oil layer has a thickness of 40 micrometers to 50 micrometers.
[0027] The thickness of the raw tung oil layer is in the range of 40 microns to 50 microns, which provides more effective corrosion protection. This thickness is sufficient to form an effective isolation layer that can effectively prevent oxygen and moisture in the air from contacting the iron powder. This thickness can prevent oxidation and corrosion reactions, thereby greatly reducing the corrosion risk of the iron powder. The raw tung oil layer of appropriate thickness can provide continuous protection and reduce material degradation caused by environmental factors (such as humidity and oxygen), thereby extending the service life of the iron powder.
[0028] The thickness of the raw tung oil layer is in the range of 40 microns to 50 microns, providing excellent adhesion. This thickness of the raw tung oil layer can ensure that the protective film is tightly attached to the surface of the iron powder particles. This thickness can enhance the stability of the protective film and prevent it from falling off or being damaged during handling, storage and use. Compared with a coating that is too thin, this thickness can effectively prevent the coating from falling off or peeling off under the action of external forces, ensuring a long-term protective effect.
[0029] The thickness of the raw tung oil layer is in the range of 40 microns to 50 microns, which improves the anti-corrosion effect. The moderate thickness ensures that the raw tung oil layer is not too thick while providing anti-corrosion protection, thereby avoiding affecting other properties of the iron powder (such as miscibility and combustion effect). This thickness can give full play to the anti-corrosion effect of the raw tung oil while maintaining good material properties. Sufficient thickness ensures that the raw tung oil layer can effectively resist corrosion factors, reduce the risk of corrosion on the surface of the iron powder caused by environmental factors, and ensure the stability of the iron powder under different storage and use conditions.
[0030] The thickness of the raw tung oil layer is in the range of 40 microns to 50 microns, which also ensures production and processing efficiency. The raw tung oil layer thickness of 40 microns to 50 microns is relatively easy to control and apply during the production process. The protective layer of moderate thickness will not significantly increase the production cost, and will not have a negative impact on other properties of the iron powder during the application process. This thickness can be evenly coated on the surface of the iron powder particles, avoiding the problem of uneven coating or local excessive thickness, and ensuring the consistency of the overall protective effect.
[0031] The thickness of the tung oil layer is in the range of 40 microns to 50 microns, which improves the quality of the final product. The appropriate thickness of the tung oil layer can effectively maintain the performance stability of the iron powder in applications such as fireworks. It provides sufficient protection to ensure that the iron powder is not affected by corrosion during storage and use, thereby maintaining its original physical and chemical properties. In fireworks applications, the appropriate thickness of the tung oil layer can maintain the good performance of the iron powder, thereby improving the visual effect and firing effect of the fireworks. Too thick a coating may affect the combustion performance, while the appropriate thickness can maintain the best lighting effect.
[0032] As a result, the raw tung oil layer thickness is in the range of 40 microns to 50 microns, providing excellent anti-corrosion protection, enhanced adhesion and effective protective performance. It can ensure that the raw tung oil layer plays the best role in protecting the iron powder while maintaining good production and processing efficiency. By providing a moderate thickness, the raw tung oil layer can effectively isolate environmental factors, extend the service life of the iron powder, and ensure the quality and performance of the final product.
[0033] According to some embodiments of the present invention, the thickness of the raw tung oil layer is any value of 40 microns, 41 microns, 42 microns, 43 microns, 44 microns, 45 microns, 46 microns, 47 microns, 48 microns, 49 microns, 50 microns, or a range formed by any two of them, such as 45 microns to 48 microns.
[0034] According to some embodiments of the present invention, the thickness of the anti-rust oil layer is 20 micrometers to 30 micrometers.
[0035] The thickness of the anti-rust oil layer is 20 microns to 30 microns, which can effectively block the direct damage of moisture and oxygen in the environment to the iron powder. Although the thickness is thin, it is enough to provide additional protection, supplement the anti-corrosion effect of the raw tung oil layer, and ensure that the iron powder remains stable in various environments.
[0036] The thickness of the anti-rust oil layer is 20 microns to 30 microns. Together with the thicker raw tung oil layer, the anti-rust oil layer provides a second line of defense, making the iron powder more resistant to various corrosion sources. It can supplement the insufficient protection of the raw tung oil layer and provide more comprehensive anti-corrosion protection.
[0037] Due to the thin thickness of the anti-rust oil layer, it usually does not significantly affect other properties of the iron powder, such as its mixability and processability. The thin layer thickness can maintain the handling properties of the iron powder while providing anti-rust protection.
[0038] Compared with a thicker protective layer, a thinner anti-rust oil layer can reduce excessive coverage of iron powder particles and avoid possible interference with the burning effect of fireworks.
[0039] A 20-30 micron anti-rust oil layer is easier to control during production and is applied more evenly. Compared to thicker coatings, this thickness does not cause unevenness or excessive thickness during handling and processing. The application of a thin layer requires less anti-rust oil, which reduces production costs. A thinner anti-rust layer can achieve the desired protection effect while reducing material consumption.
[0040] Although the anti-rust oil layer is thin, it can further improve the anti-corrosion performance on the basis of the raw tung oil layer. It not only provides additional protection, but also ensures the long-term stability of the iron powder under different environmental conditions. In combination with the thicker raw tung oil layer, the moderate thickness of the anti-rust oil layer can enhance the overall protective combination effect, allowing the iron powder to maintain good performance during storage and use.
[0041] In applications such as fireworks, a moderate thickness of anti-rust oil layer can ensure the stability of iron powder during the firing process and optimize the visual effect without affecting its luminous brightness and overall performance.
[0042] Therefore, the benefits of a 20 to 30 micron thick anti-rust oil layer include providing specialized anti-rust protection, reducing the impact on other properties of iron powder, facilitating production and processing, maintaining anti-corrosion performance, and improving the quality of the final product. It forms an effective double-layer protection mechanism by combining it with a thicker layer of raw tung oil. The thicker protection of the raw tung oil layer is mainly responsible for preventing oxidation and corrosion, while the thinner protection of the anti-rust oil layer further supplements the anti-rust effect. The two work together to achieve comprehensive protection of the iron powder. This design ensures that the iron powder can maintain good performance and stability during long-term storage and use.
[0043] According to some embodiments of the present invention, the thickness of the anti-rust oil layer is any value of 20 microns, 21 microns, 22 microns, 23 microns, 24 microns, 25 microns, 26 microns, 27 microns, 28 microns, 29 microns, 30 microns, or a range formed by any two of them, such as 25 microns to 28 microns.
[0044] The second aspect of the present invention provides a method for preparing the anticorrosive iron powder of the first aspect of the present invention, comprising the following steps:
[0045] S1: After heating the iron powder particle matrix, adding raw tung oil and mixing evenly to obtain iron powder with the raw tung oil layer coated on the surface;
[0046] S2: After cooling the iron powder obtained in step S1, add anti-rust oil, mix well and let stand to obtain the anti-corrosion iron powder.
[0047] The method for preparing anti-corrosion iron powder of the present invention has multiple beneficial effects by sequentially coating the raw tung oil layer and the anti-rust oil layer on the iron powder particle matrix. These effects not only improve the anti-corrosion performance of the iron powder, but also optimize the production process and the quality of the final product. The following are the detailed beneficial effects:
[0048] This method achieves double protection by first heating and coating with raw tung oil, and then adding anti-rust oil after cooling. The raw tung oil layer provides the main isolation from oxygen and moisture, and the anti-rust oil layer provides additional anti-rust protection on this basis. Such a double-layer structure can significantly improve the corrosion resistance of the iron powder and ensure its stability under different environmental conditions. The double-layer protection mechanism effectively reduces the risk of oxidation and corrosion of the iron powder, thereby extending its service life. This improvement is especially important for iron powder that needs to be stored and transported for a long time, and can significantly reduce the performance degradation caused by corrosion.
[0049] This method simplifies the production process of anti-corrosion iron powder by using heating and cooling steps. Heating allows the raw tung oil to better penetrate and adhere to the surface of the iron powder particles, while cooling solidifies the protective layer to form a stable coating structure. This method avoids complex processing steps, making the production process more efficient and economical. During the heating process, the raw tung oil can be evenly coated on the surface of the iron powder particles, ensuring the uniformity of the protective layer. Adding anti-rust oil after cooling helps to form a consistent anti-rust layer. This process ensures the consistency and reliability of the final product.
[0050] Through efficient mixing and standing steps, it is possible to ensure that each step of the processing is uniform and effective, thereby reducing material waste. This optimized production process reduces production costs and improves economic benefits. The double-layer protection structure of the anti-corrosion iron powder gives the final product excellent anti-corrosion performance. This ensures the stability of the iron powder in the application, especially in fields with strict requirements on anti-corrosion performance (such as fireworks manufacturing), to ensure that its performance is not affected by environmental changes.
[0051] The preparation method ensures the quality and stable performance of the iron powder. Due to the uniformity and effectiveness of the anti-corrosion layer, the final product can maintain consistent performance during use, avoiding problems caused by uneven anti-corrosion effects. In applications such as fireworks, the excellent performance of anti-corrosion iron powder directly improves the firing effect and visual impact. Through scientific preparation methods, it is ensured that the iron powder can exert the best brightness and color effects during the combustion process, thereby improving the ornamental value of the product.
[0052] Through effective anti-corrosion treatment, the potential safety hazards caused by iron powder corrosion are reduced. Especially during transportation and storage, the double-layer protection structure can reduce the risk of unexpected reactions and material failure, thereby improving the safety of operation and use.
[0053] The preparation method of the present invention does not require expensive equipment and complex process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, is suitable for enterprises of different sizes, and is easy to industrialize.
[0054] According to some embodiments of the present invention, in step S1, the amount of raw tung oil added is 10 wt% to 17 wt% of the mass of the iron powder.
[0055] The addition of 10wt% to 17wt% of raw tung oil ensures the formation of a protective layer of sufficient thickness to effectively isolate the iron powder from contact with air and moisture. This thickness can provide sufficient anti-corrosion protection while avoiding the negative effects that may be caused by too thick a coating (such as interference with the performance of the iron powder).
[0056] According to some embodiments of the present invention, in step S1, the heating temperature is 180°C to 200°C.
[0057] At temperatures between 180°C and 200°C, the viscosity of raw tung oil is significantly reduced, giving it better fluidity and permeability. In this way, the raw tung oil can be more evenly coated on the surface of the iron powder particles, forming a uniform protective layer. Higher temperatures speed up the reaction of raw tung oil with iron powder, making the coating process more efficient. This reduces production time, improves production efficiency, and ensures the uniformity of the raw tung oil layer.
[0058] In addition, when heated to a temperature range of 180℃ to 200℃, raw tung oil can cure quickly to form a stable protective layer. The cured raw tung oil layer has good adhesion and durability, and can effectively prevent oxidation and corrosion of iron powder. The raw tung oil layer cured within this temperature range has good chemical and physical stability, and can maintain its protective effect during subsequent processing and use. The temperature range of 180℃ to 200℃ can avoid other adverse chemical reactions that may occur at higher temperatures, such as excessive oxidation or deterioration of raw tung oil. This helps to maintain the anti-corrosion properties of raw tung oil while avoiding potential negative effects on iron powder particles.
[0059] Furthermore, within the temperature range of 180°C to 200°C, the heating process is relatively safe and is not likely to cause overheating and decomposition of raw tung oil or generate harmful gases, which reduces possible safety hazards in the production process.
[0060] According to some embodiments of the present invention, in step S2, the cooling temperature is 30°C to 50°C.
[0061] Cooling within the temperature range of 30℃ to 50℃ can avoid uneven adhesion of the anti-rust oil layer due to excessive cooling speed. This temperature range provides a stable environment, which helps the anti-rust oil to be evenly coated on the raw tung oil layer, thereby forming a stable anti-rust layer. The moderate cooling temperature can avoid the fall-off or peeling between the anti-rust oil layer and the raw tung oil layer caused by drastic temperature changes, ensuring that the anti-rust oil layer can firmly adhere to the surface of the iron powder.
[0062] Raw tung oil has the characteristics of fast drying, good fluidity and strong adhesion. It can penetrate the irregular surface of iron powder very well and achieve full coverage. After coating, anti-rust oil is added. Based on the principle of similar compatibility, the interface between anti-rust oil and tung oil will form a mutually soluble structure, and there is no obvious interface, which enhances the adhesion of the coating. The prepared coating layer has a large thickness, good density, good water and oxygen barrier ability and stability, thereby improving the long-term resistance of iron powder materials to salt water and salt spray corrosion. Cooling within the temperature range of 30℃ to 50℃ is conducive to the formation of a mutually soluble structure at the interface between rust oil and tung oil, enhancing the adhesion of the coating.
[0063] According to some embodiments of the present invention, in step S2, the amount of the anti-rust oil added is 2 wt% to 8 wt% of the mass of the iron powder.
[0064] The amount of anti-rust oil added within this range can ensure good mixing with the raw tung oil layer and uniform coating. Too little anti-rust oil may not form an effective protective layer, while too much anti-rust oil may cause uneven coating or material waste. The addition amount of 2wt% to 8wt% provides the best balance.
[0065] According to some embodiments of the present invention, in step S2, the standing time is 1 to 2 days.
[0066] The third aspect of the present invention provides a firework, wherein the raw materials for preparing the firework include the anti-corrosion iron powder of the first aspect of the present invention or the anti-corrosion iron powder prepared by the method of the second aspect of the present invention.
[0067] One of the technical solutions of the present invention regarding fireworks has at least the following beneficial effects:
[0068] The excellent performance of the anti-corrosion iron powder ensures that the fireworks emit uniform and strong light effects when ignited. The iron powder can produce bright yellow light when burning, and the anti-corrosion treatment ensures that the iron powder can emit light stably under various environmental conditions and is not affected by moisture or oxidation, thereby improving the overall brightness and color performance of the fireworks, so that the fireworks of the present invention have enhanced light effects, stable brightness and color.
[0069] Due to the excellent stability of the anti-corrosion iron powder, the effect of each firework can be consistent. In this way, consumers can enjoy consistent visual effects and viewing experience in different usage occasions (such as festivals, celebrations, etc.). BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is a physical picture of the anti-corrosion iron powder just prepared in Example 1.
[0071] Figure 2 This is a real picture of the anti-corrosion iron powder prepared in Example 1 after being naturally placed in the air for 24 months.
[0072] Figure 3 This is a microscopic photograph of the anticorrosive iron powder of Example 1. DETAILED DESCRIPTION
[0073] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0074] In the first aspect, some embodiments of the present invention provide an anti-corrosion iron powder, including an iron powder particle matrix, the surface of the iron powder particle matrix is sequentially coated with a raw tung oil layer and an anti-rust oil layer, and the thickness of the raw tung oil layer is greater than the thickness of the anti-rust oil layer.
[0075] It should be noted that the core of the anti-corrosion iron powder of the present invention lies in the double-layer protection structure on its surface, including a raw tung oil layer and an anti-rust oil layer. This double-layer protection mechanism provides two layers of protection, specifically:
[0076] Raw tung oil (also known as tung oil) is a natural vegetable oil with excellent anti-corrosion properties. The raw tung oil layer is relatively thick, which enables it to effectively isolate air and moisture, thereby preventing the iron powder from coming into contact with oxygen and moisture during storage and use. The drying and anti-corrosion properties of tung oil can effectively delay the oxidation of iron powder and reduce the occurrence of corrosion. Raw tung oil has the characteristics of fast drying, good fluidity and strong adhesion. It can penetrate the irregular surface of iron powder very well and achieve full wrapping; after coating, anti-rust oil is added. Using the principle of similar compatibility, the interface between the anti-rust oil and tung oil will form a mutually soluble structure, and there is no obvious interface, which enhances the adhesion of the coating. The prepared coating layer has a large thickness, good density, good water and oxygen barrier capabilities and stability, thereby improving the iron powder material's ability to resist salt water and salt spray corrosion for a long time.
[0077] Anti-rust oil is a kind of grease specially used to prevent metal corrosion, which is usually thin. The anti-rust oil layer can further provide protection to prevent iron powder from rusting during long-term storage and transportation. Since the anti-rust oil layer is thinner than the raw tung oil layer, it mainly plays a supplementary protective role and will not affect the main protective function of the raw tung oil layer.
[0078] The thickness of the raw tung oil layer is greater than the anti-rust oil layer. This design ensures a long-lasting and comprehensive anti-corrosion effect. The thickness of the raw tung oil layer can effectively prevent the intrusion of moisture and oxygen, while the anti-rust oil layer provides additional protection and enhances the comprehensive anti-corrosion performance of the iron powder. This structure can not only prevent short-term corrosion, but also improve the stability of the iron powder during long-term storage and transportation.
[0079] The anti-corrosion iron powder of the present invention can exhibit excellent anti-corrosion performance under various environmental conditions. For example, in a humid environment, the tung oil layer can effectively prevent the intrusion of moisture, while the anti-rust oil layer can deal with other potential corrosion sources. This adaptability enables the iron powder to maintain good performance under different storage and use conditions.
[0080] Due to the double layer protection, the anti-corrosion iron powder of the present invention is more stable during transportation and storage. During transportation, especially in a humid or high temperature environment, the double protection of the thickness of the raw tung oil layer and the anti-rust oil layer can reduce the corrosion risk of the iron powder and reduce the safety hazards caused by the degradation of the performance of the iron powder.
[0081] In the application of fireworks, the stability of iron powder directly affects the effect of fireworks. If the iron powder is oxidized or corroded during use, the light effect of the fireworks will decrease, or even abnormal firing will occur. Through the double-layer anti-corrosion treatment of the present invention, the iron powder can maintain good performance during long-term storage and transportation, thereby ensuring that the effect of fireworks is not affected. Furthermore, through effective anti-corrosion treatment, the service life of the iron powder is extended. This not only improves the comprehensive performance of the iron powder, but also reduces the additional cost caused by material corrosion, making the production and use of fireworks more economical and reliable.
[0082] Thus, the anti-corrosion iron powder of the present invention provides excellent anti-corrosion performance through the dual protection of the raw tung oil layer and the anti-rust oil layer. The thick protection of the raw tung oil layer ensures the long-term stability of the iron powder, while the anti-rust oil layer further enhances the protective effect. This design not only improves the storage and transportation stability of the iron powder, but also ensures the firing effect of the fireworks in actual use, thereby improving the quality and safety of the fireworks.
[0083] It should also be noted that the anti-corrosion iron powder of the present invention adopts a double-layer protection structure, including a raw tung oil layer and an anti-rust oil layer, and has significant resistance to chloride ion corrosion. Specifically:
[0084] The raw tung oil layer is the main protective layer of the anti-corrosion iron powder. It is thick and can effectively isolate the chloride ions in the external environment. - ) is a common corrosive medium, especially in salt spray environment. Raw tung oil has excellent adhesion and permeability, and can form a dense protective layer on the surface of iron powder particles. This protective film effectively prevents direct contact between chloride ions and iron powder, thereby slowing down the corrosion reaction caused by chloride ions.
[0085] The rust-proof oil layer provides an additional layer of protection on top of the raw tung oil layer. This rust-proof oil has a protective function and can resist mild chloride ion corrosion. Although the rust-proof oil layer is thin, its function is to form a miscible structure with the raw tung oil layer, further enhancing the protective effect. The rust-proof oil can fill the tiny gaps that may exist in the raw tung oil layer, provide an additional shielding effect, and reduce the penetration path of chloride ions in the raw tung oil layer, thereby improving the overall resistance to chloride ion corrosion.
[0086] The double-layer protective structure of the raw tung oil layer and the anti-rust oil layer not only plays its own role, but also forms a synergistic effect. The raw tung oil layer effectively isolates most of the chloride ions, while the anti-rust oil layer further protects against chloride ions that may penetrate the raw tung oil layer. Since there is no obvious interface between the anti-rust oil layer and the raw tung oil layer, this mutually soluble structure reduces the risk of chloride ion intrusion, thereby significantly enhancing the comprehensive resistance to chloride ion corrosion.
[0087] In practical applications, the anti-corrosion iron powder of the present invention exhibits excellent corrosion resistance in a chlorine-containing environment. For example, in a salt spray test, the iron powder exhibits a lower corrosion rate and a longer corrosion resistance time. This indicates that the dual protection of the raw tung oil layer and the anti-rust oil layer effectively delays the corrosion of the iron powder by chloride ions, ensuring the stability and long-term reliability of the iron powder in a harsh environment.
[0088] In the fireworks manufacturing process, the anti-corrosion performance of iron powder directly affects the quality and safety of the product. Chloride ion corrosion may cause the performance of iron powder to deteriorate during storage and transportation, thereby affecting the firing effect of fireworks. Through the double-layer protection of the anti-corrosion iron powder of the present invention, the iron powder can maintain excellent performance in a chlorine-containing environment, thereby ensuring the light effect and firing effect of fireworks in actual use, and improving the safety and reliability of fireworks.
[0089] Therefore, the anti-corrosion iron powder of the present invention is protected by the dual layers of raw tung oil and anti-rust oil, which not only effectively blocks moisture and oxygen, but also has significant resistance to chloride ion corrosion. This design makes the iron powder have better stability and reliability during storage, transportation and application, and improves its overall performance.
[0090] In combination with the first aspect, in some embodiments of the present invention, the particle size of the iron powder particle matrix is 100 micrometers to 300 micrometers.
[0091] The particle size of the iron powder matrix is in the range of 100 to 300 microns, which optimizes the combustion effect. The iron powder particle size of 100 to 300 microns is moderate, which is neither as easy to form excessive dust as too fine powder, nor as difficult to burn evenly as too large particles. The moderate particle size can ensure that the iron powder burns more evenly and stably during the fireworks, enhancing the light effect and effect of the fireworks. Medium-sized iron powder particles can effectively dissipate heat and produce more dazzling light during the combustion process. Too fine particles may cause too fast combustion and reduce the brightness; too large particles may cause incomplete combustion and insufficient brightness. The moderate particle size can provide the best light effect.
[0092] The particle size of the iron powder particle matrix ranges from 100 microns to 300 microns, which improves the stability of the fireworks. Iron powder with medium particle size is not easy to form a large amount of dust in the air, and has a lower risk of flying and volatilization than finer powders. This reduces the risk of dust generated during manufacturing, storage and transportation, thereby improving the safety of operations. Particles that are too small are prone to static electricity, increasing safety hazards; particles that are too large are difficult to mix evenly, affecting the performance of fireworks. Medium particle size iron powder provides a good balance to ensure the stability of the material.
[0093] The particle size of the iron powder particle matrix ranges from 100 microns to 300 microns, which improves the material's handling and processing properties. Medium-sized iron powder can be mixed well with other fireworks ingredients (such as oxidizers and developers). Particles that are too large may cause uneven mixing and affect the final firing effect; while particles that are too small may increase processing difficulty and cost. Iron powder of this size is easier to handle during production and processing, which can improve production efficiency and reduce production costs. The moderate particle size ensures consistency and stability during mixing, pressing and other processing processes.
[0094] The particle size of the iron powder particle matrix is in the range of 100 microns to 300 microns, which optimizes the anti-corrosion performance. The particle size of 100 microns to 300 microns can effectively adapt to the coating of the anti-corrosion coating. For example, the protective layer formed by the raw tung oil layer and the anti-rust oil layer on the surface of the iron powder of this particle size is uniform and effective, providing a good anti-corrosion effect. If the particle size is too small, the coating may not be evenly distributed, and if the particle size is too large, the coating may not adhere firmly. Through the appropriate particle size, the protective effect of the anti-corrosion layer can be optimized, thereby extending the service life of the iron powder and reducing performance degradation and safety hazards caused by corrosion.
[0095] The particle size of the iron powder matrix is in the range of 100 microns to 300 microns, which improves the visual effect of fireworks. The appropriate particle size can produce uniform light and color effects in fireworks. Too small particle size may cause uneven light scattering, while too large particle size may cause unstable combustion effect. The appropriate iron powder particles can provide a more stable and bright visual effect, improving the viewing value of fireworks.
[0096] Therefore, the particle size of the iron powder particle matrix in the range of 100 microns to 300 microns provides multiple beneficial effects, including optimizing combustion effects, improving the stability of fireworks, enhancing the handling of materials, optimizing anti-corrosion performance, and enhancing the visual effects of fireworks. This particle size of iron powder can achieve the best combustion effect and performance while ensuring safety and processing efficiency, and is the appropriate particle size range.
[0097] In combination with the first aspect, in some embodiments of the present invention, the particle size of the iron powder particle matrix is any value of 100 microns, 150 microns, 200 microns, 250 microns, 300 microns, or a range formed by any two of them, such as 150 microns to 250 microns.
[0098] In combination with the first aspect, in some embodiments of the present invention, the thickness of the raw tung oil layer is 40 micrometers to 50 micrometers.
[0099] It should be noted that the thickness of the raw tung oil layer is in the range of 40 microns to 50 microns, which provides more effective anti-corrosion protection. This thickness is sufficient to form an effective isolation layer that can effectively prevent oxygen and moisture in the air from contacting the iron powder. This thickness can prevent oxidation reactions and corrosion reactions, thereby greatly reducing the corrosion risk of the iron powder. The raw tung oil layer of moderate thickness can provide continuous protection and reduce material degradation caused by environmental factors (such as humidity and oxygen), thereby extending the service life of the iron powder.
[0100] It should also be noted that the thickness of the raw tung oil layer is in the range of 40 microns to 50 microns, providing excellent adhesion. This thickness of the raw tung oil layer can ensure that the protective film is tightly attached to the surface of the iron powder particles. This thickness can enhance the stability of the protective film and prevent it from falling off or being damaged during handling, storage and use. Compared with a coating that is too thin, this thickness can effectively prevent the coating from falling off or peeling off under the action of external forces, ensuring a long-term protective effect.
[0101] In addition, the thickness of the raw tung oil layer is in the range of 40 microns to 50 microns, which improves the anti-corrosion effect. The moderate thickness ensures that the raw tung oil layer is not too thick while providing anti-corrosion protection, thereby avoiding affecting other properties of the iron powder (such as miscibility and combustion effect). This thickness can give full play to the anti-corrosion effect of the raw tung oil while maintaining good material properties. Sufficient thickness ensures that the raw tung oil layer can effectively resist corrosion factors, reduce the risk of corrosion on the surface of the iron powder caused by environmental factors, and ensure the stability of the iron powder under different storage and use conditions.
[0102] Furthermore, the thickness of the raw tung oil layer is in the range of 40 microns to 50 microns, which also ensures production and processing efficiency. The raw tung oil layer thickness of 40 microns to 50 microns is relatively easy to control and apply during the production process. A protective layer of moderate thickness will not significantly increase production costs, and will not have a negative impact on other properties of the iron powder during application. This thickness can be evenly coated on the surface of the iron powder particles, avoiding the problem of uneven coating or local excessive thickness, and ensuring the consistency of the overall protective effect.
[0103] Furthermore, the thickness of the tung oil layer is in the range of 40 microns to 50 microns, which improves the quality of the final product. The appropriate thickness of the tung oil layer can effectively maintain the performance stability of the iron powder in applications such as fireworks. It provides sufficient protection to ensure that the iron powder is not affected by corrosion during storage and use, thereby maintaining its original physical and chemical properties. In fireworks applications, the appropriate thickness of the tung oil layer can maintain the good performance of the iron powder, thereby improving the visual effect and firing effect of the fireworks. Too thick a coating may affect the combustion performance, while the appropriate thickness can maintain the best light effect.
[0104] As a result, the raw tung oil layer thickness is in the range of 40 microns to 50 microns, providing excellent anti-corrosion protection, enhanced adhesion and effective protective performance. It can ensure that the raw tung oil layer plays the best role in protecting the iron powder while maintaining good production and processing efficiency. By providing a moderate thickness, the raw tung oil layer can effectively isolate environmental factors, extend the service life of the iron powder, and ensure the quality and performance of the final product.
[0105] In combination with the first aspect, in some embodiments of the present invention, the thickness of the raw tung oil layer is any value of 40 microns, 41 microns, 42 microns, 43 microns, 44 microns, 45 microns, 46 microns, 47 microns, 48 microns, 49 microns, 50 microns, or a range formed by any two of them, such as 45 microns to 48 microns.
[0106] In combination with the first aspect, in some embodiments of the present invention, the thickness of the anti-rust oil layer is 20 microns to 30 microns.
[0107] It can be understood that the thickness of the anti-rust oil layer is 20 microns to 30 microns, which can effectively block the direct damage of moisture and oxygen in the environment to the iron powder. Although the thickness is thin, it is enough to provide additional protection, supplement the anti-corrosion effect of the raw tung oil layer, and ensure that the iron powder remains stable in various environments.
[0108] It should be noted that the thickness of the anti-rust oil layer is 20 microns to 30 microns. Together with the thicker raw tung oil layer, the anti-rust oil layer provides a second line of defense, making the iron powder more resistant to various corrosion sources. It can supplement the insufficient protection of the raw tung oil layer and provide more comprehensive anti-corrosion protection.
[0109] It should also be noted that due to the thin thickness of the anti-rust oil layer, it usually does not significantly affect other properties of the iron powder, such as its mixability and processability. The thinner layer thickness can maintain the handling performance of the iron powder while providing anti-rust protection.
[0110] Compared with a thicker protective layer, a thinner anti-rust oil layer can reduce excessive coverage of iron powder particles and avoid possible interference with the burning effect of fireworks.
[0111] A 20-30 micron anti-rust oil layer is easier to control during production and is applied more evenly. Compared to thicker coatings, this thickness does not cause unevenness or excessive thickness during handling and processing. The application of a thin layer requires less anti-rust oil, which reduces production costs. A thinner anti-rust layer can achieve the desired protection effect while reducing material consumption.
[0112] Although the anti-rust oil layer is thin, it can further improve the anti-corrosion performance on the basis of the raw tung oil layer. It not only provides additional protection, but also ensures the long-term stability of the iron powder under different environmental conditions. In combination with the thicker raw tung oil layer, the moderate thickness of the anti-rust oil layer can enhance the overall protective combination effect, allowing the iron powder to maintain good performance during storage and use.
[0113] In applications such as fireworks, a moderate thickness of anti-rust oil layer can ensure the stability of iron powder during the firing process and optimize the visual effect without affecting its luminous brightness and overall performance.
[0114] Therefore, the benefits of a 20 to 30 micron thick anti-rust oil layer include providing specialized anti-rust protection, reducing the impact on other properties of iron powder, facilitating production and processing, maintaining anti-corrosion performance, and improving the quality of the final product. It forms an effective double-layer protection mechanism by combining it with a thicker layer of raw tung oil. The thicker protection of the raw tung oil layer is mainly responsible for preventing oxidation and corrosion, while the thinner protection of the anti-rust oil layer further supplements the anti-rust effect. The two work together to achieve comprehensive protection of the iron powder. This design ensures that the iron powder can maintain good performance and stability during long-term storage and use.
[0115] In combination with the first aspect, in some embodiments of the present invention, the thickness of the anti-rust oil layer is any value of 20 microns, 21 microns, 22 microns, 23 microns, 24 microns, 25 microns, 26 microns, 27 microns, 28 microns, 29 microns, 30 microns, or a range formed by any two of them, such as 25 microns to 28 microns.
[0116] In a second aspect, in some embodiments of the present invention, there is provided a method for preparing the anticorrosive iron powder of the first aspect of the present invention, comprising the following steps:
[0117] S1: After heating the iron powder particle matrix, adding raw tung oil and mixing evenly to obtain iron powder with a raw tung oil layer on the surface;
[0118] S2: After cooling the iron powder obtained in step S1, add anti-rust oil, mix well and let stand to obtain anti-corrosion iron powder.
[0119] It can be understood that the method for preparing anti-corrosion iron powder of the present invention has many beneficial effects by coating the raw tung oil layer and the anti-rust oil layer on the iron powder particle matrix in sequence. These effects not only improve the anti-corrosion performance of the iron powder, but also optimize the production process and the quality of the final product. The following are the detailed beneficial effects:
[0120] This method achieves double protection by first heating and coating with raw tung oil, and then adding anti-rust oil after cooling. The raw tung oil layer provides the main isolation from oxygen and moisture, and the anti-rust oil layer provides additional anti-rust protection on this basis. Such a double-layer structure can significantly improve the corrosion resistance of the iron powder and ensure its stability under different environmental conditions. The double-layer protection mechanism effectively reduces the risk of oxidation and corrosion of the iron powder, thereby extending its service life. This improvement is especially important for iron powder that needs to be stored and transported for a long time, and can significantly reduce the performance degradation caused by corrosion.
[0121] This method simplifies the production process of anti-corrosion iron powder by using heating and cooling steps. Heating allows the raw tung oil to better penetrate and adhere to the surface of the iron powder particles, while cooling solidifies the protective layer to form a stable coating structure. This method avoids complex processing steps, making the production process more efficient and economical. During the heating process, the raw tung oil can be evenly coated on the surface of the iron powder particles, ensuring the uniformity of the protective layer. Adding anti-rust oil after cooling helps to form a consistent anti-rust layer. This process ensures the consistency and reliability of the final product.
[0122] Through efficient mixing and standing steps, it is possible to ensure that each step of the processing is uniform and effective, thereby reducing material waste. This optimized production process reduces production costs and improves economic benefits. The double-layer protection structure of the anti-corrosion iron powder gives the final product excellent anti-corrosion performance. This ensures the stability of the iron powder in the application, especially in fields with strict requirements on anti-corrosion performance (such as fireworks manufacturing), to ensure that its performance is not affected by environmental changes.
[0123] The preparation method ensures the quality and stable performance of the iron powder. Due to the uniformity and effectiveness of the anti-corrosion layer, the final product can maintain consistent performance during use, avoiding problems caused by uneven anti-corrosion effects. In applications such as fireworks, the excellent performance of anti-corrosion iron powder directly improves the firing effect and visual impact. Through scientific preparation methods, it is ensured that the iron powder can exert the best brightness and color effects during the combustion process, thereby improving the ornamental value of the product.
[0124] Through effective anti-corrosion treatment, the potential safety hazards caused by iron powder corrosion are reduced. Especially during transportation and storage, the double-layer protection structure can reduce the risk of unexpected reactions and material failure, thereby improving the safety of operation and use.
[0125] The preparation method of the present invention does not require expensive equipment and complex process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, is suitable for enterprises of different sizes, and is easy to industrialize.
[0126] In combination with the second aspect, in some embodiments of the present invention, in step S1, the amount of raw tung oil added is 10 wt % to 17 wt % of the mass of the iron powder.
[0127] The addition of 10wt% to 17wt% of raw tung oil ensures the formation of a protective layer of sufficient thickness to effectively isolate the iron powder from contact with air and moisture. This thickness can provide sufficient anti-corrosion protection while avoiding the negative effects that may be caused by too thick a coating (such as interference with the performance of the iron powder).
[0128] In combination with the second aspect, in some embodiments of the present invention, in step S1, the heating temperature is 180°C to 200°C.
[0129] At temperatures between 180°C and 200°C, the viscosity of raw tung oil is significantly reduced, giving it better fluidity and permeability. In this way, the raw tung oil can be more evenly coated on the surface of the iron powder particles, forming a uniform protective layer. Higher temperatures speed up the reaction of raw tung oil with iron powder, making the coating process more efficient. This reduces production time, improves production efficiency, and ensures the uniformity of the raw tung oil layer.
[0130] In addition, when heated to a temperature range of 180℃ to 200℃, raw tung oil can cure quickly to form a stable protective layer. The cured raw tung oil layer has good adhesion and durability, and can effectively prevent oxidation and corrosion of iron powder. The raw tung oil layer cured within this temperature range has good chemical and physical stability, and can maintain its protective effect during subsequent processing and use. The temperature range of 180℃ to 200℃ can avoid other adverse chemical reactions that may occur at higher temperatures, such as excessive oxidation or deterioration of raw tung oil. This helps to maintain the anti-corrosion properties of raw tung oil while avoiding potential negative effects on iron powder particles.
[0131] Furthermore, within the temperature range of 180°C to 200°C, the heating process is relatively safe and is not likely to cause overheating and decomposition of raw tung oil or generate harmful gases, which reduces possible safety hazards in the production process.
[0132] In combination with the second aspect, in some embodiments of the present invention, in step S2, the cooling temperature is 30°C to 50°C.
[0133] Cooling within the temperature range of 30℃ to 50℃ can avoid uneven adhesion of the anti-rust oil layer due to excessive cooling speed. This temperature range provides a stable environment, which helps the anti-rust oil to be evenly coated on the raw tung oil layer, thereby forming a stable anti-rust layer. The moderate cooling temperature can avoid the fall-off or peeling between the anti-rust oil layer and the raw tung oil layer caused by drastic temperature changes, ensuring that the anti-rust oil layer can firmly adhere to the surface of the iron powder.
[0134] Raw tung oil has the characteristics of fast drying, good fluidity and strong adhesion. It can penetrate the irregular surface of iron powder very well and achieve full coverage. After coating, anti-rust oil is added. Based on the principle of similar compatibility, the interface between anti-rust oil and tung oil will form a mutually soluble structure, and there is no obvious interface, which enhances the adhesion of the coating. The prepared coating layer has a large thickness, good density, good water and oxygen barrier ability and stability, thereby improving the long-term resistance of iron powder materials to salt water and salt spray corrosion. Cooling within the temperature range of 30℃ to 50℃ is conducive to the formation of a mutually soluble structure at the interface between rust oil and tung oil, enhancing the adhesion of the coating.
[0135] In combination with the second aspect, in some embodiments of the present invention, in step S2, the amount of anti-rust oil added is 2wt% to 8wt% of the mass of the iron powder.
[0136] The amount of anti-rust oil added within this range can ensure good mixing with the raw tung oil layer and uniform coating. Too little anti-rust oil may not form an effective protective layer, while too much anti-rust oil may cause uneven coating or material waste. The addition amount of 2wt% to 8wt% provides the best balance.
[0137] In conjunction with the third aspect, in some embodiments of the present invention, a firework is provided, wherein the raw materials for preparing the firework include the anti-corrosion iron powder of the first aspect of the present invention or the anti-corrosion iron powder prepared by the method of the second aspect of the present invention.
[0138] It should be noted that the excellent performance of the anti-corrosion iron powder ensures that the fireworks emit uniform and strong light effects when ignited. The iron powder can produce bright yellow light when burning, and the anti-corrosion treatment ensures that the iron powder can emit light stably under various environmental conditions and is not affected by moisture or oxidation, thereby improving the overall brightness and color performance of the fireworks, so that the fireworks of the present invention have enhanced light effects, stable brightness and color.
[0139] Due to the excellent stability of the anti-corrosion iron powder, the effect of each firework can be consistent. In this way, consumers can enjoy consistent visual effects and viewing experience in different usage occasions (such as festivals, celebrations, etc.).
[0140] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0141] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0142] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0143] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0144] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0145] The iron powder in the examples and comparative examples is commercially available common cast iron powder, with a carbon content of 3% to 4%. It should be noted that the iron powder particle matrix in the anti-corrosion iron powder of the present invention can be not only common cast iron powder, but also iron powder of different grades and types.
[0146] The raw tung oil in the embodiments and comparative examples is commercially available common raw tung oil.
[0147] The anti-rust oil in the examples and comparative examples is commercially available NS100 anti-rust oil.
[0148] Example 1
[0149] Provided is an anti-corrosion iron powder, comprising an iron powder particle matrix, the surface of which is sequentially coated with a raw tung oil layer and an anti-rust oil layer, wherein the thickness of the raw tung oil layer is greater than that of the anti-rust oil layer.
[0150] The particle size of the iron powder particle matrix is 100 microns to 300 microns.
[0151] The thickness of the raw tung oil layer is 45 microns.
[0152] The thickness of the anti-rust oil layer is 25 microns.
[0153] The specific preparation method is:
[0154] S1. The cast iron powder raw material is sieved to remove impurities and small-sized powders, with a particle size range of 100 to 300 μm;
[0155] S2. Weighing: Weigh the appropriate amount of iron powder according to production requirements;
[0156] S3. Heating: Put the weighed iron powder into a stainless steel container, heat and stir-fry, and heat the entire iron powder to 190°C.
[0157] S4. Adding raw tung oil: After the heated iron powder is removed from the heat source, add 13% (relative to the weight ratio of the iron powder) of raw tung oil and stir quickly to make the entire raw tung oil evenly cover the surface of the iron powder. The time is about 20 minutes. During the stirring process, the iron powder will slowly cool down;
[0158] S5. Add anti-rust oil: When the iron powder is cooled to 40°C, add 5% NS100 anti-rust oil and stir for 10 minutes, cool naturally and dry;
[0159] S6. After the iron powder is left for one day, a dense and strong coating is formed on the surface of the iron powder.
[0160] Figure 1 This is a physical picture of the anticorrosive iron powder just prepared in Example 1. Figure 1It can be seen that the iron powder has uniform color, without obvious particle aggregation or color inconsistency, indicating that the uniform coating effect during the preparation process is good. In terms of particle morphology, it can be observed that the iron powder particles are uniform and have no agglomeration, indicating that the iron powder is properly handled during the preparation process and the anti-corrosion layer is evenly covered.
[0161] Figure 2 This is a photo of the anti-corrosion iron powder prepared in Example 1 after being placed in the air for 24 months. Figure 2 It can be seen that the iron powder has no obvious change, the color is still uniform, and there is no obvious particle aggregation or color inconsistency, indicating that the uniform coating effect during the preparation process is good. In terms of particle morphology, it can be observed that the iron powder particles are uniform and have no agglomeration, indicating that the iron powder is properly handled during the preparation process and the anti-corrosion layer is evenly covered.
[0162] In addition, from Figure 2 It can also be observed that after the anti-corrosion iron powder was placed in the air for 24 months, the surface of the iron powder was shiny, and the uniform surface gloss indicated the uniform coating of the anti-corrosion layer. The color of the iron powder did not change, indicating that the stability and anti-corrosion properties of the coating were excellent.
[0163] Figure 3 is a microscopic picture of the anticorrosive iron powder prepared in Example 1. Figure 3 It can be seen that the coating is tightly attached to the surface of the iron powder particles without peeling or falling off, indicating that the coating has good adhesion. In addition, no cracks, bubbles or discontinuous areas were observed, indicating that the surface coating of the iron powder particles is in good condition, the coating is evenly covered, and there is no exposure of the iron powder matrix.
[0164] Example 2
[0165] The difference from Example 1 is that during the preparation process, the amount of raw tung oil added is 17%, and the amount of NS100 anti-rust oil added is 8%.
[0166] Example 3
[0167] The difference from Example 1 is that during the preparation process, the amount of raw tung oil added is 10%, and the amount of NS100 anti-rust oil added is 2%.
[0168] Comparative Example 1
[0169] Compared with Example 1, only raw tung oil is added, and no anti-rust oil is added. The specific preparation method is:
[0170] S1. The cast iron powder raw material is sieved to remove impurities and small-sized powders, with a particle size range of 100 to 300 μm;
[0171] S2. Weighing: Weigh the appropriate amount of iron powder according to production requirements;
[0172] S3. Heating: Put the weighed iron powder into a stainless steel container, heat and stir-fry, and heat the entire iron powder to 180°C to 200°C;
[0173] S4. Adding raw tung oil: After the heated iron powder is removed from the heat source, add 13% (by weight) raw tung oil and stir quickly to evenly cover the surface of the iron powder with the raw tung oil for about 20 minutes. Then cool it down, and the iron powder will slowly dry during the stirring process.
[0174] Comparative Example 2
[0175] Compared with Example 1, only antirust oil is added, and raw tung oil is not added. The specific preparation method is:
[0176] S1. The cast iron powder raw material is sieved to remove impurities and small-sized powders, with a particle size range of 100 to 300 μm;
[0177] S2. Weighing: Weigh the appropriate amount of iron powder according to production requirements;
[0178] S3. Heating: Put the weighed iron powder into a stainless steel container, heat and stir-fry, and heat the entire iron powder to 30°C to 50°C;
[0179] S4. Add anti-rust oil: Add 5% NS100 anti-rust oil and stir for 10 to 12 minutes, cool naturally and dry.
[0180] Comparative Example 3
[0181] Compared with Example 1, the rust-proof oil is added first, and then the tung oil is added, and the adding order is different. The specific preparation method is:
[0182] S1. The cast iron powder raw material is sieved to remove impurities and small-sized powders, with a particle size range of 100 to 300 μm;
[0183] S2. Weighing: Weigh the appropriate amount of iron powder according to production requirements;
[0184] S3. Heating: Put the weighed iron powder into a stainless steel container, heat and stir-fry, and heat the entire iron powder to 40°C.
[0185] S4. Add anti-rust oil: Add 5% NS100 anti-rust oil and stir for 10 minutes;
[0186] S5. Adding raw tung oil: Continue heating the iron powder to 190°C, add 13% (by weight) raw tung oil and stir quickly to evenly cover the surface of the iron powder with the raw tung oil for about 20 minutes. After the heated iron powder is removed from the heating source, the iron powder will slowly cool down during the stirring process.
[0187] Performance Testing
[0188] The anti-corrosion iron powder for fireworks prepared in the examples and comparative examples was subjected to a sodium chloride corrosion resistance test. The specific method is:
[0189] S1. Weighing: 10g sodium chloride; 100mL tap water; 10g coated cast iron powder;
[0190] S2. Test: Place 10g of sodium chloride in 100mL of tap water and stir to dissolve. Place the coated cast iron powder in the above solution, shake well, and shake for 10 minutes. Drain off most of the water and place it on a cement floor or filter paper;
[0191] S3. Time: In the above test, the coated cast iron powder shall be qualified if it does not turn yellow, red or rust for 10 days.
[0192] The results are shown in Table 1.
[0193] Table 1
[0194]
[0195] As can be seen from Table 1, the anticorrosive iron powder in Example 1 is double-coated (raw tung oil layer and antirust oil layer), the raw tung oil layer is 45 microns thick, and the antirust oil layer is 25 microns thick. Such a design provides a strong and stable protective effect. The raw tung oil layer can be well combined with the iron powder to form a stable protective film, and the antirust oil layer further enhances the protective effect. According to the test results, the anticorrosive iron powder of Example 1 performed well in the salt water resistance test, and no yellowing or rusting occurred within 10 days, meeting the standard requirements. This shows that it has a good anticorrosion effect and can effectively resist corrosion caused by sodium chloride.
[0196] Although the same proportion of raw tung oil was used in Comparative Example 1, the lack of the dual protection of the anti-rust oil layer significantly reduced the anti-corrosion performance. Although the raw tung oil layer can provide basic protection, its protective effect is limited when used alone, especially in a humid and salt water environment. The test results show that the anti-corrosion iron powder of Comparative Example 1 turned yellow within 3 days, and the iron powder began to rust. This shows that the raw tung oil layer alone cannot provide sufficient anti-corrosion protection, especially in an environment containing sodium chloride, the protective effect is significantly insufficient.
[0197] Comparative Example 2 lacks a raw tung oil layer, and only uses anti-rust oil. Although this single anti-rust oil layer has a certain protective effect, its protective effect is significantly insufficient compared to the double-layer protection of Example 1. The lack of basic protection of the raw tung oil layer results in weak protective ability. In the test, the anti-corrosion iron powder of Comparative Example 2 turned yellow and rusted within 1 day. This shows that the use of anti-rust oil alone cannot provide sufficient protection, especially when exposed to salt water for a long time, the anti-corrosion performance of the iron powder decreases rapidly.
[0198] Due to the improper order of addition, the uniformity and stability of the protective layer in Comparative Example 3 were affected. The rust-proof oil was added first and then the raw tung oil, resulting in the rust-proof oil failing to effectively form a protective layer on the surface of the iron powder. In the test, Comparative Example 3 showed yellowing after 7 days and some iron powder rusted. Although the added raw tung oil and rust-proof oil improved the protective effect to a certain extent, it was not as significant as the double-layer protective effect in Example 1.
[0199] The anti-corrosion iron powder of the present invention has a thick coating layer, good density, good water and oxygen barrier capabilities and stability, thereby improving the iron powder material's ability to resist salt water and salt spray corrosion for a long time.
[0200] The present invention also provides a firework, the raw materials for preparing the firework include the anti-corrosion iron powder of the first aspect of the present invention or the anti-corrosion iron powder prepared by the method of the second aspect of the present invention. The excellent performance of the anti-corrosion iron powder ensures that the firework emits a uniform and strong light effect when it is ignited. The iron powder can produce bright yellow light when burning, and the anti-corrosion treatment ensures that the iron powder can emit light stably under various environmental conditions and is not affected by moisture or oxidation, thereby improving the overall brightness and color performance of the firework, so that the firework of the present invention has enhanced light effect, stable brightness and color.
[0201] After testing, it was found that due to the excellent stability of the anti-corrosion iron powder, the effect of each ignition of the fireworks can be kept consistent, ensuring that consumers can enjoy a consistent visual effect and viewing experience when the fireworks are set off.
[0202] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. An anticorrosive iron powder, characterized in that: It comprises an iron powder particle matrix, the surface of which is sequentially coated with a raw tung oil layer and an anti-rust oil layer, wherein the thickness of the raw tung oil layer is greater than that of the anti-rust oil layer.
2. The anticorrosive iron powder according to claim 1, characterized in that: The particle size of the iron powder particle matrix is 100 microns to 300 microns.
3. The anticorrosive iron powder according to claim 1 or 2, characterized in that: The thickness of the raw tung oil layer is 40 microns to 50 microns.
4. The anticorrosive iron powder according to claim 1 or 2, characterized in that: The thickness of the anti-rust oil layer is 20 microns to 30 microns.
5. A method for preparing the anticorrosive iron powder according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: After heating the iron powder particle matrix, adding raw tung oil and mixing evenly to obtain iron powder with the raw tung oil layer coated on the surface; S2: After cooling the iron powder obtained in step S1, add anti-rust oil, mix well and let stand to obtain the anti-corrosion iron powder.
6. The method according to claim 5, characterized in that In step S1, the amount of raw tung oil added is 10wt% to 17wt% of the mass of the iron powder.
7. The method according to claim 5, characterized in that In step S1, the heating temperature is 180°C to 200°C.
8. The method according to claim 5, characterized in that In step S2, the cooling temperature is 30°C to 50°C.
9. The method according to claim 5, characterized in that In step S2, the amount of the anti-rust oil added is 2wt% to 8wt% of the mass of the iron powder.
10. A firework, characterized in that: The raw materials for preparing the fireworks include the anti-corrosion iron powder according to any one of claims 1 to 4 or the anti-corrosion iron powder prepared by the method according to any one of claims 5 to 9.
